Fundamentals of expenses’ non-deductibility in the companies' income tax law: Portuguese’s case - Aldeia, Susana (2020)
This paper aims to understand what kind of fundamentals can justify the tax adjustments imposed by the Portuguese Corporate Income Tax Law. For this purpose, it analyzes the legal dispositions and doctrine, particularly, it examines Portugal data sources: the Corporate Income Tax Law (Código do Imposto sobre o Rendimento das Pessoas Coletivas - CIRC) and doctrinal's understandings. The results show that doctrinal interpretations identifies four reasons to tax correction. They are the technical and practical reasons, the separation between corporate and personal equity, the formal reasons; and the disincentive of the no moralistic behavior. This study helps to know better the corporate income tax’s particularities. Although it is a relevant contribution to international tax law literature, and countries can analyze this experience and collet it to its profit, it only researches the Portugal case.